2014
DOI: 10.2967/jnumed.114.140871
|View full text |Cite
|
Sign up to set email alerts
|

Preclinical Evaluation of Robotic-Assisted Sentinel Lymph Node Fluorescence Imaging

Abstract: An ideal substance to provide convenient and accurate targeting for sentinel lymph node (SLN) mapping during robotic-assisted surgery has yet to be found. We used an animal model to determine the ability of the FireFly camera system to detect fluorescent SLNs after administration of a dual-labeled molecular imaging agent. Methods We injected the footpads of New Zealand White rabbits with 1.7 or 8.4 nmol of tilmanocept labeled with 99mTc and a near-infrared fluorophore, IRDye800CW. One and 36 h after injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
1
14
0
Order By: Relevance
“…This study, based on examination of 36 LNs, demonstrated that the FireFly fluorescence imaging system is capable of detecting fluorescent-labeled tilmanocept up to 38 h after a submucosal injection into the porcine urinary bladder. This result is consistent with fluorescence imaging of SLNs 36 h after fluorescent tilmanocept injection into the footpad of rabbits (20) and the canine prostate gland (18).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This study, based on examination of 36 LNs, demonstrated that the FireFly fluorescence imaging system is capable of detecting fluorescent-labeled tilmanocept up to 38 h after a submucosal injection into the porcine urinary bladder. This result is consistent with fluorescence imaging of SLNs 36 h after fluorescent tilmanocept injection into the footpad of rabbits (20) and the canine prostate gland (18).…”
Section: Discussionsupporting
confidence: 87%
“…We used injections into the submucosal layer of the bladder wall, which has significantly different lymphatic drainage than the foot-pads of the rabbit. Although the previous study (20) used the same fluorescence imaging system/camera, the pelvic LNs that drain the bladder wall are embedded within a layer of fat that envelopes major blood vessels or nerves, an anatomic setting that differs greatly from rabbit popliteal LNs that reside between muscle layers. As a result, the animal model used in the current work provides a far more realistic and demanding challenge to successful fluorescence imaging.…”
Section: Discussionmentioning
confidence: 99%
“…There have been a couple of reports on robotic sentinel‐node navigation surgery using fluorescence imaging with indocyanine green (ICG) etc. carried out with near‐infrared fluorescence imaging technology built into the robotic platform optical system (Firefly Fluorescence Imaging Scope; Intuitive Surgical, Inc.) . Laparoscopic and endoscopic cooperative surgery (LECS) may develop into robotic and endoscopic cooperative surgery (RECS) in the near future.…”
Section: Future Perspectives On Robotic Upper Gi Surgerymentioning
confidence: 99%
“…carried out with near-infrared fluorescence imaging technology built into the robotic platform optical system (Firefly Fluorescence Imaging Scope; Intuitive Surgical, Inc.). [94][95][96] Laparoscopic and endoscopic cooperative surgery (LECS) may develop into robotic and endoscopic cooperative surgery (RECS) in the near future.…”
Section: Application Of the Surgical Robot To Function-preserving Surmentioning
confidence: 99%
“…This agent has shown some promises in preoperative planning by PET/CT and intraoperative guidance via fluorescence. 82,83…”
Section: Highly Probable Slns: This Includes Nodes Appearingmentioning
confidence: 99%